Social Mobility in the Balkans: Border Policing Practices Are Potentially Letting Through Mostly the Members of the “Elite Club” - Tibor Bardóczy (Köz-gazdaság)
Countless articles and books have been written so far about migration and its effect on countries. This topic is currently one of the most important ones among scholars from different fields of study, especially among social scientists. Although it has been almost eighty years since the end of the Second World War, certain regions are not peaceful even now. The Russian-Ukrainian conflict and the Israeli-Palestinian War are causing migration waves, which will inevitably force people to leave their homes in the hope of better faith. Because of its actuality, this book with its approach might provide interesting and useful lessons about migration, even beyond the Western Balkans. Naturally, migration cannot be narrowed down to one discipline, it equally concerns economics and sociology, as well as criminology and police science. Even though the Western Balkan and the south-eastern region of the Schengen area, which is the gate of Europe, is a hotspot when it comes to migration, there are not many papers focusing on this region. This is why the book Border Policing and Security Technologies: Mobility and Proliferation of Borders in the Western Balkans is highly relevant and actual, as it attempts to fill this gap.